Effectiveness of a video-based intervention to improve the interpersonal communication skills of public health midwives in a district of Sri Lanka: a cluster randomised trial - S A S Prasanna; H T C S Abeysena; M A A P Alagiyawanna (BMJ Public Health)
Objective To determine the effectiveness of a video-based intervention, the V-BIS, in improving the interpersonal communication skills (IPCS) of public health midwives (PHMs).Design A cluster randomised trial.Setting The setting is a Medical Officer of Health (MOH) area, the district’s basic administrative unit in public health. The study was conducted at six MOH areas/clusters in a district of Sri Lanka between February and July 2020.Participants PHMs who completed 6 months of working in the same setting were recruited.Intervention The V-BIS intervention is a video-based intervention designed to improve the IPCS of PHMs.Main outcome measures The primary outcome was the proportion of PHMs having good IPCS 1 month after the intervention. The secondary outcomes were (1) the proportion of PHMs having ‘good IPCS’ 3 months after the intervention and (2) the proportion of PHMs having ‘good knowledge of complementary feeding (CF)’ practices 1 month after the intervention.Results Compared with the control group, the intervention group improved their IPCS by 33.0% at 1 month and 18.3% at 3 months after the intervention. The observed differences in skills between the groups were statistically significant at 1 month (adjusted OR=14.00, 95% CI 4.9 to 40.1) and 3 months (adjusted OR=5.52, 95% CI 1.81 to 16.9). Compared with the control group, the intervention group did not significantly improve good knowledge of CF practices 1 month after the intervention (OR=2.61, 95% CI 0.65 to 10.53).Conclusions The V-BIS intervention effectively improves the IPCS of PHMs and can be used as a training intervention.Trial registration number SLCTR/2020/006.